Ethiopia's Land Rental Market Partners Survey, 2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset is a follow-up for households who were visited during Feed the Future I (FtF) Ethiopia end-line Survey 2018 and who participated in land rental market in Tigray and Amhara regions. Participation in the land rental market is defined as if a household rented in, sharecropped in, rented out or sharecropped out at least one parcel. The land rental market partners of 730 FtF end-line households (with 1551 parcels) were visited in land rental market partners survey in 2019. The partners survey covered 739 households and 2,745 parcels. Even if the partners survey is conducted few months later after FtF end-line survey, it follows the same time period and data collection instrument which is consistent with FtF end-line survey. A structured household questionnaire was used to collect household, plot, and individual level data. The questionnaire modules cover household characteristics, land use (crop production), input use, labor, livestock ownership, shocks, off-fam employment, access to credit, ownership of productive equipment’s and remittances. This dataset, combined with the main FtF end-line 2018 data, enables to assess land rental market interactions between landlords and tenants.